Violence, The Effect of Cartoons on the Child’s Emotional Development - Susanu, Neaga (New Trends in Psychology, 2022)
Violence is generally defined as any intentional or accidental action that causes psychological or physical harm to oneself or another person, animals or objects. The child in front of the TV does not have the usual experience of language, the dialogic stimulation of thinking and reflection that parents, grandparents or the human environment in general offer. The visual and auditory stimuli perceived in front of the small screen are so aggressive, they follow one another so quickly that they exceed the brain’s ability to control them. The animation has its origins in the old Asian shadow theater and returned in force around 1832. The principle on which it was based was to make drawings whose succession formed a moving image. Cartoons are not considered the only cause of violence in today’s society, but they are a factor that leads to violent habits. In addition to the immediate effects that cartoons have on the child, psychological research has shown many long-term effects on the child’s behavior. Exposure to TV violence followed by exposure to video game violence leads to higher levels of aggression than the two variables taken separately.